Buyer-Driven Knowledge Transfer Activities to Enhance Organizational Sustainability of Suppliers - Usama Awan; Amira Khattak; Sajeela Rabbani; Amandeep Dhir (MDPI, 2022)
Despite the significant contribution of buyer-driven knowledge transfer activities (BDKTAs) to innovation and operational performance, studies that analyze social sustainability in manufacturing (suppliers) firms are still scarce. This paper examines the mediation relationship of knowledge acquisition and investment in environmental management between BDKTAs and social performance improvements (SPIs). The paper contributes to the understanding of buyer knowledge transfer activities, with a focus on the knowledge acquisition capabilities and investments in environmental management, and the effect on SPIs. The hypotheses were examined with partial least squares structural equation modeling (PLS-SEM) with data collected from 239 firms. Buyer knowledge transfer activities are likely to increase the willingness of suppliers to make specific environmental investments into operations in waste reduction procedures, the recycling of materials, and pollution prevention training of employees. We proposed that buyer knowledge transfer activities are necessary to survive and grow and thus there is a need to acquire knowledge resources to achieve organizational sustainability. Buyer knowledge transfer activities are necessary to make investment decisions in environmental management programs. Firms that focus on buyer knowledge transfer activities and internal investments into environmental management can attain sustainability objectives.